CNF dispersion resin composition and producing method therefor, as well as, inkjet recording head using the composition and producing method therefor

By dispersing cellulose nanofibers in curable resins using a method that involves adding a liquid resin to water-dispersed CNF and evaporating moisture while stirring, the limitations of existing dispersion methods are overcome, resulting in improved mechanical properties and expanded application possibilities for CNF in curable resin compositions.

JP2025062238APending Publication Date: 2025-04-14CANON KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023171168
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing methods for dispersing cellulose nanofibers (CNF) in curable resins are limited, often requiring water and resulting in poor dispersion outside of aqueous systems, which restricts the range of usable curable materials and impairs mechanical properties.

Method used

A method involving the addition of a liquid resin to water-dispersed CNF, followed by evaporation of moisture while stirring, allows for the dispersion of CNF in curable resins with nano-order particle sizes without the need for water, thereby expanding the range of usable curable materials and enhancing mechanical properties.

Benefits of technology

This approach enables the production of a curable resin composition with improved transparency and mechanical properties, including high elastic modulus and hardness, even with a small amount of CNF, and allows for the use of CNF in applications where water cannot be evaporated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062238000001_ABST
    Figure 2025062238000001_ABST
Patent Text Reader

Abstract

To provide a method for producing a CNF dispersion curable resin composition, the method being capable of dispersing cellulose nanofibers (CNF) into a nano-order particle size in resin without using water, improving mechanical properties even with a small amount of CNF addition, and largely expanding the range of curable material selection.SOLUTION: A method for dispersing CNF into a curable resin is characterized by adding a liquid resin or a liquid resin composition to CNF that has been defibrillated and dispersed in water, and evaporating moisture while stirring.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for dispersing cellulose nanofibers (hereinafter referred to as CNF) in a curable resin at nano-order particle sizes, a curable resin composition in which CNF is nano-dispersed using said method, and an inkjet recording head using said resin composition and a method for manufacturing said recording head. [Background technology]

[0002] CNF can impart thixotropy to aqueous materials and is an excellent rigid fiber, so it is used as a reinforcing material for resins, etc., to improve mechanical strength. Since defibrated modified CNF cannot be dispersed in organic substances that are not highly compatible with water, including the representative TENPO oxide, CNF is used via aqueous or water-soluble organic solvents, as shown below.

[0003] Patent Document 1 discloses a coating composition containing oxidized cellulose nanofibers, a water-soluble resin, and a silane derivative compound. Patent Document 2 discloses a coating composition containing CNF, a water-miscible organic solvent, water, and a resin. Patent Document 3 discloses a CNF dispersion composition that can be uniformly dispersed in an organic material by mixing CNF dispersed in water with a water-soluble organic solvent.

[0004] In Patent Document 4, phenol and aldehydes are reacted in the presence of an acid catalyst, and a slurry of lignocellulose nanofibers is added. A method for producing a thermosetting resin composition for friction materials is disclosed in which the lignocellulose nanofibers are dispersed in a thermosetting resin while removing the dispersion medium and unreacted phenol. Patent Document 5 discloses a method for producing a polyurethane resin composition in which an aqueous dispersion of a polyurethane resin and an aqueous dispersion of cellulose nanofibers are mixed and the solvent is removed. In addition, a method for producing a polyurethane composition using a prepolymer method is applied, and an organic solvent dispersion of a urethane prepolymer having an isocyanate terminal, which is made of a polyol compound and a polyisocyanate compound, is mixed with an aqueous dispersion of cellulose nanofibers. A method for producing a polyurethane resin composition in which a polyurethane resin is produced and the solvent is removed is disclosed. As described above, in the cases of Patent Documents 4 and 5, the resins and reaction systems that can be used when dispersing CNF are limited.

[0005] In Patent Document 6, an epoxy silane coupling agent is added to an aqueous dispersion of modified CNF, and a drying process is performed to obtain lipophilic modified CNF. The lipophilic modified CNF itself is dispersible in epoxy, but since it aggregates during drying, it is difficult to disperse it at the nano-order. In this way, modified CNF is dispersed at the nano-order in water by a typical TENPO oxidation, etc., but CNF aggregates in media other than water due to poor dispersibility. Therefore, when dispersing CNF, it becomes a mixed system with water, and the materials that can be used are limited. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-033487 A [Patent Document 2] JP 2019-156864 A [Patent Document 3] JP 2023-44677 A [Patent Document 4] JP 2018-131477 A [Patent Document 5] JP 2017-128664 A [Patent Document 6] JP 2022-103970 A [Patent Document 7] JP 2014-200939 A [Patent Document 8] Japanese Patent Application Publication No. 6-286149 [Patent Document 9] Japanese Patent Application Publication No. 11-348288 Summary of the Invention [Problem to be solved by the invention]

[0007] At least one aspect of the present invention is directed to providing a method for producing a CNF-dispersed curable resin composition that can disperse CNF in a resin at nano-order particle sizes without the use of water, improves mechanical properties even with the addition of a small amount of CNF, and significantly expands the range of curable materials to be selected. At least one aspect of the present invention is directed to providing a curable resin composition prepared using the method and having excellent transparency and mechanical properties. At least one aspect of the present invention is directed to providing an inkjet recording head using the curable resin composition as a part of a member thereof, and a method for producing the same. [Means for solving the problem]

[0008] According to at least one embodiment of the present invention, there is provided a method for producing a CNF-dispersed resin composition in which CNF is dispersed in a curable resin at nano-order particle sizes, the method comprising the steps of: adding a liquid resin or a liquid resin composition that is a raw material for the curable resin to water-dispersed CNF in which defibrated CNF is dispersed in water to obtain a mixture; and evaporating water while stirring the obtained mixture.

[0009] Furthermore, according to at least one embodiment of the present invention, there is provided a curable resin composition in which defibrated CNF is dispersed in a curable resin with nano-order particle sizes, and which has physical properties including high elastic modulus and high hardness and improved mechanical strength.

[0010] According to at least one aspect of the present invention, there is provided a nozzle for ejecting ink, an ink flow path wall that communicates with the ejection port and that forms an ink flow path including an ink ejection pressure generating element; a substrate on which the ink ejection pressure generating element is formed, The ink jet recording head is characterized in that the ink flow path wall is made of the above-mentioned resin composition.

[0011] According to at least one aspect of the present invention, a method for manufacturing a liquid ejection head includes the steps of: forming an ink flow path pattern on a substrate on which ink ejection pressure generating elements are formed; forming a coating resin layer on the substrate on which the ink flow path pattern is formed, using an ink flow path wall forming member; forming an ink ejection port in the coating resin layer by photolithography; and removing the ink flow path pattern to form an ink flow path, The method for producing the CNF-dispersed resin composition provides a method for producing an inkjet recording head, characterized by using the ink flow path wall-forming member. Effect of the Invention

[0012] At least one aspect of the present invention can provide a method for producing a CNF-dispersed curable resin composition, which can disperse CNF in a resin at a nano-order particle size without using water, improve mechanical properties even with the addition of a small amount of CNF, and greatly expand the range of curable materials to be selected. At least one aspect of the present invention can provide a curable resin composition prepared using the method, which has excellent transparency and mechanical properties. At least one aspect of the present invention can provide an inkjet recording head using the curable resin composition as a part of a member, and a method for producing the same. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an ink-jet head of the present invention. [Diagram 2] 1A and 1B are diagrams illustrating a method for producing an inkjet head according to the present invention, where (a) is a perspective view, and (b) is a schematic cross-sectional view taken along line AA' in (a). [Diagram 3] FIG. 3 is a schematic cross-sectional view illustrating the method for producing an inkjet head of the present invention, continuing from FIG. 2(b). [Figure 4] FIG. 4 is a schematic cross-sectional view illustrating the method for producing an inkjet head according to the present invention, continuing from FIG. [Diagram 5] FIG. 5 is a schematic cross-sectional view illustrating the method for producing an inkjet head of the present invention, continuing from FIG. [Figure 6] FIG. 6 is a schematic cross-sectional view illustrating the method for producing an inkjet head of the present invention, continuing from FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, a method for producing a CNF-dispersed resin composition according to one embodiment of the present invention, a curable resin composition using the method, an inkjet recording head using the same, and a method for producing the same will be described in detail. However, the scope of the present invention is not limited to this embodiment, and modifications that do not depart from the gist of the present invention are also included in the present invention.

[0015] (Method of producing CNF-dispersed resin composition and CNF-dispersed resin composition obtained by the method) The present invention is a method for producing a CNF-dispersed resin composition in which cellulose nanofibers (CNF) are dispersed in a curable resin at nano-order particle sizes. The method is characterized by comprising the steps of: adding a liquid resin or a liquid resin composition, which is a raw material for the curable resin, to water-dispersed CNF obtained by dispersing defibrated CNF in water to obtain a mixture; and evaporating water while stirring the mixture obtained.

[0016] The present invention also relates to a CNF-dispersed resin composition in which defibrated CNF is dispersed in a curable resin with nano-order particle sizes, and the CNF-dispersed resin composition has physical properties including high elastic modulus and high hardness, thereby improving mechanical strength.

[0017] As the CNF that is defibrated and dispersed in water (referred to as water-dispersed CNF), the CNF is surface-modified and treated to prevent aggregation, as typified by TEMPO oxidation. Here, TEMPO oxidation refers to an oxidation method using 2,2,6,6-tetramethylpiperidine 1-oxy free radical (TEMPO), which is a stable nitroxy radical. Such CNF exhibits high thixotropy in an aqueous dispersion, but when water is evaporated from the aqueous dispersion, the CNF aggregates due to hydrogen bonding, and it is not possible to obtain a dried CNF with a nano-order particle size. On the other hand, a process is performed in which a liquid resin or a liquid resin composition, which is a raw material for a curable resin, is added to the CNF that is defibrated and dispersed in water as in the present invention to obtain a mixture. Next, a process of evaporating water while stirring the obtained mixture is performed, thereby making it possible to disperse the CNF in a nano-order particle size in the resin composition. Here, the process of obtaining a mixture and the process of evaporating water while stirring the obtained mixture may be performed in different devices, or may be performed consecutively or simultaneously in the same device. In this stirring and water evaporation process, it is preferable to stir at a higher speed and with higher shear, and it is also preferable that the water-dispersed CNF used is at a lower concentration. Specific mixing and stirring conditions are not particularly limited, but it is preferable to perform a mixing process in which revolution and rotation are performed for a certain period of time under vacuum conditions using a vacuum stirring and defoaming mixer, and stirring at high shear using a three-roll mill or the like. This stirring is performed until all the water is gone, and it is preferable to continue until the mixture becomes transparent as a target end point. At the beginning of the stirring, the mixture is opaque and close to an emulsion with a particle size of several μm, but the water evaporates as the stirring proceeds, and the emulsion-like CNF does not aggregate with each other and becomes transparent. In addition, the system may be heated during stirring, but if a mixture is obtained by adding a curing agent described later and then stirred, the system is heated to a range where the curing reaction does not proceed during stirring. In addition, a method of using a curing agent that is inactive below a certain temperature, such as a latent curing agent, and heating at a temperature below the specified temperature may be used.

[0018] In the present invention, in order to disperse CNF in resin at the nano-order level, CNF that has been defibrated and dispersed in water at the nano-order level (referred to as water-dispersed CNF) is used. Water-dispersed CNF is preferably surface-modified during defibration, and the functional groups at the modified sites are compatible with or reactive to the resin in which they are dispersed. Specific examples of modification during defibration include etherification, esterification (sulfuric acid esterification, phosphoric acid esterification), and carboxylation. In addition, among CNFs that contain crystalline and amorphous regions, CNFs that contain more crystalline regions are preferred because their structure improves dispersibility in the target resin. For example, the product name "DextraCel" manufactured by ANOMERA, which is used in the examples, is used. TM " is a cellulose nanocrystal (CNC) made by removing the amorphous regions from defibrillated CNFs through chemical treatment. This CNC is a hard, needle-like nanoparticle with a length of 100-250 nm and a width of 5-10 nm.

[0019] There are no particular limitations on the water-dispersed CNF, but it is necessary that it is defibrated and dispersed in water to have nano-order particle sizes. When CNF is dispersed in water in nano-order particle sizes, it exhibits thixotropy.

[0020] The content of CNF in the water-dispersed CNF is preferably 10% by mass or less, since it is necessary to finely disperse CNF by stirring with liquid resin or liquid resin composition (hereinafter simply referred to as liquid resin). If the content of CNF in the water-dispersed CNF is 10% by mass or less, excessive increase in thixotropy is suppressed, and CNF can be finely dispersed in the liquid resin. On the other hand, there is no particular lower limit for the content, but if it is too small, the amount of aqueous dispersion to be mixed increases, and it takes a long time to evaporate water, which will be described later. Therefore, the content of CNF in the water-dispersed CNF is preferably 1% by mass or more, and more preferably 5% by mass or more.

[0021] The liquid resin used is liquid when mixed with the water-dispersed CNF and contains raw materials for the curable resin (monomers, oligomers, etc.). The curable resin is not limited to, but may be hard acrylic resin (raw acrylic monomer), urethane resin (raw polyol), epoxy resin (raw epoxy monomer), etc. In particular, epoxy resin, which is widely used in negative resists, adhesives, sealing materials, molding materials, etc., can be preferably used. Specific examples of epoxy resins are not particularly limited as long as they have two or more epoxy groups. Examples of such epoxy resins include alicyclic epoxy resins such as 1,2-epoxy-4-(2-oxiranyl)cyclohexane adducts of 2,2-bis(hydroxymethyl)-1-butanol, as well as bisphenol-type epoxy resins, novolac-type epoxy resins, and glycidyl ester-type epoxy resins. Such epoxy resins can be used by dissolving them in a solvent as necessary, such as alcohol-based solvents such as methanol, ethanol, normal propanol, isopropyl alcohol, normal butanol, aromatic hydrocarbon-based solvents such as xylene and toluene, and glycol-based solvents such as diethylene glycol.

[0022] To improve the dispersibility of CNF in liquid resin, a silane coupling agent having a functional group similar to that of the liquid resin (raw material monomer, etc.) is added to the water-dispersed CNF. The reason why the addition of the silane coupling agent improves the dispersibility of the water-dispersed CNF in liquid resin is thought to be that the OH groups of the silane coupling agent are hydrogen-bonded or dehydrated and condensed with the OH groups of the CNF after hydrolysis, thereby weakening the aggregation between the CNFs. Therefore, it is preferable to add the silane coupling agent in an amount that is equal to or greater than the equivalent amount of OH groups of the CNF in the water-dispersed CNF. The silane coupling agent may be one in which an alkoxy group bonded to a Si atom is hydrolyzed in water to generate an OH group. In addition, it is preferable that the silane coupling agent has a functional group that is reactive with the liquid resin to be mixed. For example, a silane coupling agent having a glycidoxy group that reacts with an epoxy resin can be used. Specific examples of the silane coupling agent include the following. 3-Glycidoxypropyltrimethoxysilane (trade name: A-187 TM ), 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (product name: A-186 TM ), 3-glycidoxypropyltriethoxysilane (product name: A-1871 TM ), both manufactured by Momentive Performance Materials Japan.

[0023] As described above, a CNF-dispersed resin composition in which CNF is dispersed in a liquid resin or liquid resin composition in nano-order particle sizes can be obtained that has physical properties of high elastic modulus and high hardness and improved mechanical strength. Although not particularly limited, an example of a high elastic modulus is an elastic modulus of 3.8 GPa or more. The elastic modulus is measured at 23°C and 1 MHz using a dynamic mechanical analyzer (DMA). Furthermore, an example of a high hardness is a shear adhesive strength of 24 MPa or more. The shear adhesive strength is measured using a steel plate conforming to JIS K6850.

[0024] The amount (content) of CNF contained in the CNF-dispersed resin composition (curable resin composition) is preferably 30 to 70 mass%, more preferably 40 to 60 mass%. Within this range, mechanical strength can be improved. In addition, it is preferable that the moisture contained in the CNF-dispersed resin composition is completely removed, but moisture may remain in a range that makes the resin composition transparent and does not impair the mechanical strength of the cured resin composition. As described above, when water is evaporated from the conventional CNF dispersed in water, the CNF aggregates with each other due to hydrogen bonding, and it is not possible to obtain a dried CNF (dry powder) with a nano-order particle size. However, in the method according to the present invention, a liquid resin or liquid resin composition that is a raw material for a curable resin is added to the water-dispersed CNF to obtain a mixture, and water is evaporated while stirring the mixture, whereby the CNF can be dispersed in a nano-order particle size without water in the resin. Therefore, the CNF-dispersed resin composition according to the present invention can be used as a sealant or the like in tightly closed areas where it was difficult to use CNF because water, solvents, etc. cannot be evaporated. In addition, since CNF can be dispersed in a nano-order particle size and light transparency can be expressed, it can be suitably used as a material having photosensitivity. And, since CNF can be dispersed in a nano-order particle size, high mechanical strength can be exhibited even with the addition of a small amount of CNF.

[0025] The resin composition may contain a photoacid generating catalyst as a photosensitive material. The photoacid generating catalyst is not particularly limited, but may be a sulfonium salt type photoacid generator with high sensitivity to i-rays and h-rays. Specifically, a product name "CPI-410S" manufactured by San-Apro Co., Ltd. may be used. When heat curing is performed, an amine-based or imidazole-based basic curing agent may be used in the case of epoxy resin.

[0026] Furthermore, the CNF-dispersed resin composition is prepared by dispersing CNF in nano-order particle sizes in a liquid resin or liquid resin composition that is a raw material for a curable resin, and evaporating the water, and an epoxy resin can be suitably used as the curable resin. That is, the resin composition is preferably an epoxy resin composition containing an epoxy resin.

[0027] (Inkjet recording head and its manufacturing method) An embodiment of an inkjet recording head using the CNF-dispersed resin composition of the present invention in a coating resin layer that forms the ink flow path wall and a method for manufacturing the same will be described with reference to the drawings.

[0028] An inkjet recording head applied to an inkjet recording method (liquid jet recording method) generally comprises a plurality of minute ink ejection orifices, a liquid flow path, and a liquid ejection energy generating unit (ink ejection pressure generating element) provided in part of the liquid flow path. Conventionally, methods for producing such an ink jet recording head are known, for example, as described in Patent Documents 8 and 9.

[0029] In detail, as shown in Fig. 1, the ink jet recording head according to the present invention has an ejection port 6 for ejecting ink, and an ink flow path wall 5 which communicates with the ejection port and forms an ink flow path 4 including an ink ejection pressure generating element 2. The ink jet recording head also has a substrate 1 on which the ink ejection pressure generating element 2 is formed, and an ink supply port mask 3 and an ink supply port 7 on the back surface of the substrate 1. Here, an epoxy resin composition containing a photoacid generating catalyst is preferably used for the ink flow path wall 5 from the viewpoints of adhesion to the substrate, mechanical properties, fine processing ability for forming the ejection port, etc. Furthermore, the ink flow path wall 5 is formed from an ink flow path wall forming member containing the curable resin composition according to the present invention.

[0030] With the recent development of recording technology, inkjet recording devices are also used in the field of industrial printing, and higher speed and higher durability are required. Ink for industrial printing becomes harder to improve abrasion resistance, and if it sticks to the discharge port surface, it is necessary to remove the stuck matter with a harder blade or the like. In addition, in high-speed paper feeding, minute bending at the four corners of the paper may hit the discharge port surface. For this reason, high mechanical properties are required for the ink flow path wall forming member. On the other hand, it is difficult to improve the mechanical properties with only the resin composition, and the photosensitive properties are impaired when a filler or the like is simply added. Therefore, the resin composition in which the CNF according to the present invention is dispersed at a nano-order can be used as a material having photosensitivity because it can express light transparency, and further, it can improve mechanical strength, so it is very useful.

[0031] Next, an embodiment of a method for manufacturing an ink jet recording head according to the present invention will be described. First, as shown in FIG. 2(a), an ink ejection pressure generating element 2 is formed on a substrate 1. For example, a Si wafer with a crystal axis (100) can be used as the substrate. An ink supply port mask 3 may be provided on the back surface of the substrate. An electrothermal conversion element or a piezoelectric element can be used as the ink ejection pressure generating element. A control signal input electrode (not shown) for operating the ink ejection pressure generating element is connected to the ink ejection pressure generating element. FIG. 2(b) shows a schematic cross-sectional view taken along the line A-A' in FIG. 2(a). The following steps will also be described using a schematic cross-sectional view similar to FIG. 2(b).

[0032] Next, as shown in Fig. 3, a solid layer 8 in the shape of an ink flow path pattern is formed on the substrate 1 on which the ink ejection pressure generating elements 2 are formed. Specifically, a layer made of, for example, a positive resist is formed on the substrate, and the layer is processed into an ink flow path pattern. The solid layer can be formed of, for example, polymethylisopropenyl ketone. Processing into an ink flow path pattern can be performed by, for example, photolithography.

[0033] Next, as shown in FIG. 4, a coating resin layer 9 is formed by coating the solid layer 8 formed on the substrate 1 with the CNF-dispersed resin composition according to the present invention. The coating resin layer can be formed by a thin-film coating method such as spin coating the resin composition according to the present invention. In this case, it is preferable that the solvent that does not dissolve the solid layer 8 dissolves a curable epoxy resin and a cationic polymerization initiator, and has properties such as moderate volatility suitable for the thin-film coating method. The coating resin layer 9 may be only one layer, but may also be two or more layers. When two or more coating resin layers are formed, it is sufficient that at least one layer is formed of the polymerized and cured product of the ink flow path wall-forming member according to the present invention.

[0034] 5, the coating resin layer 9 is irradiated with i-lines or the like in a pattern to develop and remove the uncured portions, thereby forming the ejection ports 6. The cured portions become the ink flow path walls 5. Next, when a Si wafer substrate with a crystal axis (100) having an ink supply port mask 3 provided on the back surface is used, the substrate 1 is etched by Si anisotropic etching to form the ink supply port 7 (see FIG. 6).

[0035] Next, the solid layer 8 in the ink flow path pattern is dissolved to connect the ink supply port 7 and the ejection port 6, thereby forming the ink flow path 4 including the ink ejection pressure generating element 2. Then, if necessary, a heat treatment is performed to completely harden the forming member of the ink flow path wall 5, thereby obtaining the inkjet recording head shown in Fig. 1. The ink supply port mask 3 may be removed by chemical etching or the like after the ink supply port 7 is formed. EXAMPLES

[0036] The present invention will be specifically described below using examples, but the present invention is not limited to the following examples.

[0037] Resin compositions 1 to 8 were prepared using a nano-order dispersion method of CNF in a curable resin. That is, liquid epoxy resin, water-dispersed CNF, and a silane coupling agent were mixed and stirred in the ratios shown in Table 1. The ratios of each material shown in Table 1 are volume ratios. In addition, DextraCel used as the water-dispersed CNF TM The CNF content is 6.7% by mass. TM In addition to the silane coupling agent A-187 and DextraCel® in a volume ratio of 1:10, TM For each resin composition, the number of times of stirring and degassing until the resin composition became transparent, the change in state after dispersion in a triple roll mill, and the elastic modulus when cured with an imidazole-based curing agent were measured.

[0038] Dispersion was performed using a vacuum stirring / defoaming mixer (product name: V-mini300, manufactured by EME Co., Ltd.) under the following conditions: in a vacuum, revolution: 1600 rpm, rotation: 800 rpm, for 10 minutes.

[0039] Dispersion was performed using a three-roll mill (product name: 100VIII Easy Mill, manufactured by Imex Corporation) under the following conditions: rotation speed: 100 rpm, roll gap: 2 μm / 0 μm, 0 μm / -2 μm, 0 μm / -2 μm, and the mill was operated three times.

[0040] After dispersion using the triple roll mill, the epoxy resin composition was added with an imidazole-based curing agent, Curesol (registered trademark) 1B2MZ, and heat cured at 150°C for 1 hour. The curing agent was added in the ratio shown in Table 1. The elastic modulus was then measured at 23°C and 1 MHz using a dynamic viscoelasticity measuring device (DMA) (product name: DMS6100, manufactured by SII Nano Technology Inc.).

[0041] [Table 1]

[0042] Liquid resin Liquid epoxy resin A Liquid bisphenol A type epoxy resin Product name: BIS-A828, manufactured by Mitsubishi Chemical Corporation Liquid epoxy resin B: Liquid hydrogenated bisphenol A type epoxy resin Product name: YX8000, manufactured by Mitsubishi Chemical Corporation ●Silane coupling agent 3-Glycidoxypropyltrimethoxysilane Product name: A-187 TM Momentive Performance Materials Japan ●Water-dispersed CNF Aqueous dispersion of CNF with surface modified carboxylic acid, CNF concentration: 6.7% by mass Product Name:DextraCel TM , manufactured by ANOMERA Imidazole-based hardener 1-Benzyl-2-methylimidazole Product name: Curesol (registered trademark) 1B2MZ, manufactured by Shikoku Chemical Industry Co., Ltd.

[0043] The volume ratio of the water-dispersed CNF was about 1 / 10 of the liquid epoxy resin in resin compositions 1 and 2, and about 1 in resin compositions 3 to 6. In all cases, the mixture became almost transparent when the water was evaporated with stirring, which suggests that the CNF was dispersed at the nano-order.

[0044] If the volume ratio of water-dispersed CNF is large during stirring, the CNF may aggregate and become unable to disperse when the water is evaporated with stirring. Therefore, the volume ratio of water-dispersed CNF to the mixture of water-dispersed CNF and liquid epoxy resin is preferably 1 or less.

[0045] In resin compositions 3 to 6, defibrated CNF was dispersed using water-dispersed CNF at a concentration of 6.7% by mass, but no thixotropy was observed. Therefore, further dispersion was performed using a three-roll mill. In resin composition 4, to which a silane coupling agent was added, thixotropy was observed to such an extent that even when a droplet was dropped vertically, the droplet did not flow.

[0046] In order to confirm the mechanical properties of the cured product of the CNF-dispersed resin composition, the resin compositions were cured by adding a curing agent and the elastic modulus was measured for resin compositions 5 and 6. For comparison, the elastic modulus was also measured in the same manner for resin compositions 7 and 8, which did not contain CNF.

[0047] Comparing Resin Composition 5 and Resin Composition 7, the elastic modulus increased from 3.8 GPa to 4.0 GPa by adding CNF. Comparing Resin Composition 6 and Resin Composition 8, in which CNF is more finely dispersed, the elastic modulus increased significantly from 2.9 GPa to 3.8 GPa by adding CNF.

[0048] In the case of ordinary fillers, adding about 6% by mass does not affect the mechanical properties, but when CNF is dispersed in nano-order particle sizes, it can bring about changes in the mechanical properties because CNF has a fibrous structure and can be distributed throughout the material.

[0049] Next, resin compositions 9, 10, and 11 were prepared in the proportions shown in Table 2 by the same method as above, and were heat cured at 100° C. for 1 hour. Then, the elastic modulus at 25° C. and the shear adhesive strength with a steel plate in accordance with JIS K6850 were measured using a viscoelasticity measuring device (DMA) (product name: DMS6100, manufactured by SII Nano Technology Inc.).

[0050] Comparing Resin Compositions 9, 10, and 11, the elastic modulus gradually increased with increasing amount of CNF added, and the adhesive strength also gradually increased with increasing amount of CNF added.

[0051] When the fracture mode was confirmed, cohesive failure of the resin composition occurred, and because the CNF was dispersed in nano-order particle sizes, it is believed that the strength increased significantly even with the addition of a small amount. Also, because the CNF was dispersed in nano-order particle sizes, it is believed that the thickness of the adhesive layer could be minimized, achieving a good adhesive state.

[0052] [Table 2]

[0053] Latent hardener 1 Amicure MY-24 product name, manufactured by Ajinomoto Technofine Co., Ltd.

[0054] Next, resin compositions 12 and 13 were prepared in the same manner as above in the proportions shown in Table 3. Then, they were heat cured at 120°C for 1 hour and at 150°C for 2 hours. After curing, the elastic modulus at 25°C was measured using a viscoelasticity measuring device (DMA) (product name: DMS6100, manufactured by SII Nano Technology Inc.). A spring washer (spring washer No. 3) (iron, M24) was placed in a fluororesin container (35 mmφ, 10 mm height, Teflon (registered trademark)), and resin compositions 12 and 13 were further placed in it. The container was then heat-cured at 120°C for 1 hour and at 150°C for 2 hours. After being released from the fluororesin container, a thermal shock test was performed by a temperature cycle of -30°C for 1 hour and 100°C for 1 hour.

[0055] The elastic modulus of resin composition 13 containing CNF was slightly higher than that of resin composition 12 containing no CNF, but was almost equal to that of resin composition 12 containing no CNF. Meanwhile, in a thermal shock test, resin composition 12 containing no CNF cracked after 30 cycles, whereas resin composition 13 containing CNF did not crack up to 100 cycles.

[0056] In this way, by dispersing CNF in nano-order particle sizes in a curable resin according to the present invention, it is possible to improve toughness without significantly increasing the elastic modulus, even when a large amount of filler such as silica, which is a material for electrical sealing materials, is contained. Furthermore, dispersion of CNF in nano-order improves adhesive strength and significantly improves impact resistance when used for sealing purposes.

[0057] [Table 3]

[0058] Liquid acid anhydride MHPA: Methylhexahydrophthalic anhydride, product name: MH-700, manufactured by New Japan Chemical Co., Ltd.

[0059] (Inkjet recording head) Next, inkjet recording heads were produced by the following manufacturing method using a conventional ink flow path wall-forming member or an ink flow path wall-forming member containing a curable resin composition obtained by dispersing CNF in a curable resin on a nano-order scale according to the present invention, and their durability was measured.

[0060] As shown in FIG. 2(a), an ink discharge pressure generating element 2 was formed on a substrate 1. A Si wafer with a crystal axis (100) was used as the substrate. An ink supply port mask 3 was provided on the back surface of the substrate. As shown in FIG. 3, a positive resist OODUR (trade name, manufactured by Tokyo Ohka Kogyo Co., Ltd.) was applied to a thickness of 14 μm by spin coating on the substrate 1 on which the ink discharge pressure generating element 2 was formed. Then, the substrate was exposed to light using a ghi-line projection exposure device through a photomask, and developed using MP-5050 (trade name, manufactured by Hayashi Junyo Co., Ltd.) to form an ink flow path pattern 8. Then, a negative coating resin layer 9 was applied to a thickness of 25 μm by spin coating on the substrate 1 on which the ink flow path pattern 8 was formed. The coating resin layer 9 used a resin composition (conventional example) having the following composition as an ink flow path wall forming member and a CNF-dispersed resin composition (example) prepared by the method according to the present invention. Unless otherwise specified, "parts" refers to "parts by mass".

[0061] Conventional example The following materials were mixed to prepare resin composition 14. Liquid epoxy resin, product name "157S70", manufactured by Mitsubishi Chemical Corporation, 100 parts Photoacid generator Product name: CPI-410S, San-Apro Co., Ltd. 3 parts 100 parts xylene 70 parts diethylene glycol

[0062] CNF was dispersed to the nano-order in the following manner to prepare resin composition 15 of the present invention. First, 10 parts of the same liquid epoxy resin as in the conventional example was dissolved in a mixed solution of 100 parts of xylene and 70 parts of diethylene glycol. TM (trade name, manufactured by ANOMERA) was added, and the mixture was stirred 15 times for 10 minutes at 1600 rpm revolution and 800 rpm rotation in a vacuum state until the mixture became transparent. Then, 0.3 g of CPI-410S (trade name, photoacid generator, manufactured by San-Apro Co., Ltd.) was added and dissolved to prepare resin composition 15.

[0063] The above-prepared resin compositions 14 and 15 were each applied to a silicon wafer to a thickness of 10 μm, and then irradiated with 1100 J / m irradiated light using an I-line stepper through a mask having lines and spaces of 1 μm to 20 μm. 2 The film was exposed to light, and then post-baked at 80°C for 10 minutes, after which it was developed with propylene glycol monomethyl ether acetate (PGMEA) and cured at 200°C for 1 hour. When the state of the pattern was checked with a metallurgical microscope, it was found that a pattern with a minimum width of 3 μm had been formed.

[0064] Using a nanoindenter (product name: Triboindenter TI950, manufactured by Bruker), viscoelasticity was measured up to 100 nm at frequencies of 5, 50, and 500 Hz. As a result, there was no significant difference between frequencies, with the conventional example without added CNF having a viscoelasticity of about 6 GPa, and the present invention with added CNF having a viscoelasticity of about 7 GPa.

[0065] In this way, by dispersing CNF in nano-order particle sizes in a conventional negative resist, mechanical properties can be improved without reducing resolution. For example, when forming a nozzle flow path by patterning as shown in Patent Document 5, the nozzle flow path is subjected to mechanical shocks such as paper jams or wiping of ink deposits, so this method is suitable for improving the mechanical properties of such fine patterns.

[0066] It is also possible to use other nano-fillers in combination. For example, when nano-silica is used in combination, several tens of mass percent of it must be added, but the hardness can be increased. Therefore, the improved toughness of the CNF fibers and the improved hardness of the silica result in a material with high mechanical strength.

[0067] Next, the coating was applied to a thickness of 25 μm by spin coating. It was exposed to light by an i-line stepper through a photomask, and developed with a mixture of 60% by volume of xylene and 40% by volume of MIBK (methyl isobutyl ketone). After that, it was baked in an oven at 140° C. for 60 minutes and hardened to form the discharge port 6.

[0068] Next, a protective material OBC (trade name, manufactured by Tokyo Ohka Kogyo Co., Ltd.) was applied to a thickness of 40 μm by spin coating so that the entire front and side surfaces of the substrate 1 were covered. After that, an ink supply port 7 was formed on the back surface of the substrate 1 using the ink supply port mask 3 as a mask. Specifically, the back surface SiO2 film, which serves as the starting surface for anisotropic etching, was etched for 15 minutes using buffered hydrofluoric acid (trade name: BHF-U, manufactured by Daikin Industries, Ltd.) to form an opening in the ink supply port mask 3. Then, TMAH-22 (trade name, manufactured by Kanto Chemical Co., Ltd., tetramethylammonium hydroxide) adjusted to a temperature of 83°C was used as an anisotropic etching solution to etch the back surface of the substrate 1. <111> The etching was performed along the surface. The etching was performed until a sacrificial layer (not shown) formed on the surface of the substrate 1 for etching adjustment was completely removed. A heat storage layer or a protective layer for retaining heat from the ink discharge pressure generating element 2, which is an electrothermal converter, may be formed on the sacrificial layer. The etching time is Thickness of substrate 1 (μm) ÷ Etching rate (μm / min) The time calculated was used. Then, the etching mask layer 3 was removed from the back surface of the substrate 1 by chemical dry etching. Next, the heat storage layer near the sacrificial layer was removed using buffered hydrofluoric acid (product name: BHF-U), and the protective layer near the sacrificial layer was further removed by chemical dry etching. Then, the protective material OBC was removed with xylene. Next, the substrate 1 was immersed in methyl lactate adjusted to 40°C, and ultrasonic waves of 200 kHz and 200 W were applied to elute the ink flow path pattern 8 from the ink ejection port 6, forming the ink flow path 4 and the ink flow path wall 5. Finally, the substrate was baked in an oven at 200°C for 60 minutes to complete the curing. Through the above steps, an inkjet recording head was manufactured (see FIG. 1).

[0069] The nozzle surface of the completed inkjet recording head was wiped under strict dry conditions with a rubber blade made of hydrogenated nitrile rubber (HNBR), with a rubber hardness of 70 and a thickness of 1 mm, at a speed of 80 mm / s and a pressure of 1 mm.The nozzle surface of the inkjet recording head was then observed using a microscope every 50 wipes.

[0070] In the inkjet recording head prepared using resin composition 14 prepared in the conventional example, wear was observed on the surface of the inkjet recording head after 1500 wipes, whereas in the inkjet recording head prepared using resin composition 15 of the present invention, no change was observed even after 2500 wipes. [Explanation of symbols]

[0071] 1 Board 2. Ink ejection pressure generating element 3 Ink supply port mask 4 Ink flow path 5 Ink flow path wall 6 Outlet 7 Ink supply port

Claims

1. A method for producing a CNF-dispersed resin composition in which CNF is dispersed in a curable resin at nano-order particle sizes, the method comprising the steps of: adding a liquid resin or liquid resin composition that is a raw material for the curable resin to water-dispersed CNF in which defibrated CNF is dispersed in water to obtain a mixture; and evaporating the water while stirring the obtained mixture.

2. A method for producing a CNF-dispersed resin composition according to claim 1, further comprising the steps of adding a silane coupling agent to the water-dispersed CNF, stirring the mixture, and then adding the liquid resin or liquid resin composition to obtain the mixture.

3. The method for producing a CNF-dispersed resin composition according to claim 2 , wherein the silane coupling agent is added in an amount that provides an amount of OH groups equivalent to or greater than the amount of OH groups of the CNF in the water-dispersed CNF.

4. The method for producing a CNF-dispersed resin composition according to claim 1 or 2, wherein the CNF content in the water-dispersed CNF is 10 mass% or less.

5. The method for producing a CNF-dispersed resin composition according to claim 1 or 2, wherein the CNF-dispersed resin composition has photosensitivity.

6. The method for producing a CNF-dispersed resin composition according to claim 1 or 2, wherein the curable resin is an epoxy resin.

7. A curable resin composition in which defibrated CNF is dispersed in a curable resin with nano-order particle sizes, the curable resin composition having physical properties of improved mechanical strength with a high elastic modulus and high hardness.

8. The CNF-dispersed resin composition according to claim 7, wherein the CNF content in the curable resin composition is 30 to 70 mass%.

9. The CNF-dispersed resin composition according to claim 7 , further comprising a silane coupling agent.

10. The CNF-dispersed resin composition according to claim 7 , wherein the curable resin is an epoxy resin.

11. An ejection port for ejecting ink; an ink flow path wall that communicates with the ejection port and that forms an ink flow path including an ink ejection pressure generating element; a substrate on which the ink ejection pressure generating element is formed, An ink jet recording head, wherein the ink flow path wall is made of the CNF-dispersed resin composition according to any one of claims 7 to 10.

12. forming an ink flow path pattern on a substrate on which ink ejection pressure generating elements are formed; forming a coating resin layer on the substrate on which the ink flow path pattern is formed, using an ink flow path wall forming member; forming an ink ejection port in the coating resin layer by photolithography; and removing the ink flow path pattern to form an ink flow path, A method for manufacturing an inkjet recording head, comprising using an ink flow path wall forming member according to the method for manufacturing a CNF-dispersed resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Production of ink jet recording head

    JP1994286149A

  • Ink jet head and substrate therefor

    JP1999348288A

  • Ink jet recording head, and manufacturing method of the same

    JP2014200939A

  • Polyurethane resin composition, and method for producing the same

    JP2017128664A

  • Thermosetting resin composition for friction material, friction material and method for producing thermosetting resin composition for friction material

    JP2018131477A